2018
DOI: 10.1080/08941939.2017.1422575
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and Magnesium Sulfate: A Good Combination Treatment for Acute Lung Injury?

Abstract: The antioxidant and anti-inflammatory effects of Dex and MgSO ameliorated the detrimental effects of HCI-induced ALI. However, adverse effects on hemodynamics and lung damage were observed when the two drugs were administered together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…Magnesium sulfate inhibits inflammatory molecules including chemokine (macrophage inflammatory protein-2), cytokine (Interleukin-6, IL-6), prostaglandin E2, and cyclooxygenase-2 in lung tissue possibly by inhibiting L-type calcium channels ( Kao et al, 2011 ). In a model of acute lung injury, magnesium sulfate (150 mg/kg, intraperitoneally) ameliorates hydrochloric acid-induced lung histopathology including peribronchial inflammatory cell infiltration, alveolar septal infiltration, alveolar edema, and alveolar exudation ( Güzel et al, 2019 ). It also significantly restores oxidative stress and inflammatory response in lipopolysaccharides-induced acute lung injury of mice ( Li et al, 2019 ).…”
Section: Prevention and Treatment Of Magnesium For Lung Symptoms And mentioning
confidence: 99%
See 3 more Smart Citations
“…Magnesium sulfate inhibits inflammatory molecules including chemokine (macrophage inflammatory protein-2), cytokine (Interleukin-6, IL-6), prostaglandin E2, and cyclooxygenase-2 in lung tissue possibly by inhibiting L-type calcium channels ( Kao et al, 2011 ). In a model of acute lung injury, magnesium sulfate (150 mg/kg, intraperitoneally) ameliorates hydrochloric acid-induced lung histopathology including peribronchial inflammatory cell infiltration, alveolar septal infiltration, alveolar edema, and alveolar exudation ( Güzel et al, 2019 ). It also significantly restores oxidative stress and inflammatory response in lipopolysaccharides-induced acute lung injury of mice ( Li et al, 2019 ).…”
Section: Prevention and Treatment Of Magnesium For Lung Symptoms And mentioning
confidence: 99%
“… Lung injury Kao et al (2011) - Sprague-Dawley rats Magnesium sulfate infusion Intravenous injection of 10, 50, or 100 mg/kg magnesium sulfate Magnesium sulfate attenuates oxidative stress, inflammation, and lung injury induced by lower limb ischemia-reperfusion; magnesium sulfate mitigates lung injury induced by bilateral lower limb ischemia-reperfusion in rats, possibly inhibiting L-type calcium channels. Güzel et al (2019) - Sprague-Dawley rats Magnesium sulfate infusion Intraperitoneal injection of magnesium sulfate at 150 mg/kg Magnesium sulfate and dexmedetomidine ameliorates hydrochloric acid-induced acute lung injury vis anti-oxidation and anti-inflammation; magnesium sulfate shows greater improvement in the pathology of acute lung injury than dexmedetomidine. Note: [a] No country is mentioned in the paper.…”
Section: Prevention and Treatment Of Magnesium For Lung Symptoms And mentioning
confidence: 99%
See 2 more Smart Citations
“…In clinics, Dex is used as an anxiety reducing, sedative, and pain medication. Recently, several studies have reported that Dex could be used to attenuate acute lung injury in animal models …”
Section: Discussionmentioning
confidence: 99%